1997
DOI: 10.3354/dao029057
|View full text |Cite
|
Sign up to set email alerts
|

Proteases in pathogenic and nonpathogenic haemoflagellates, Cryptobia spp. (Sarcomastigophora:Kinetoplastida), of fishes

Abstract: Proteases were detected in Cryptobia salmositica (pathogenic and nonpathogenic vaccine strains), C. bullocki, and C. catostorni using azocasein and hide powder azure as substrates. Maximum activity occurred in acidic pH and the pathogenic strain of C, salmositica had the highest activity.Cysteine protease was found in pathogenic and nonpathogenic Cryptobia spp., but metallo-protease was only present in the pathogenic strain of C. salmositica. Five enzyrnatic bands were detected in the pathogenic C. salmositica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…infected fish are not anaemic) after 1 yr of serial in vitro cultivation (Woo & Li 1990). We (Zuo & Woo 1997a) also found a significant loss of the metallo-protease ifi the parasite after 10 mo of continuous in vitro culture and suggested that the decrease in metallo-protease is related to the loss of virulence. In the present study we purified the metallo-protease (200 kDa) from the pathogenic C. salrnositica and confirmed its proteolytic activities.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…infected fish are not anaemic) after 1 yr of serial in vitro cultivation (Woo & Li 1990). We (Zuo & Woo 1997a) also found a significant loss of the metallo-protease ifi the parasite after 10 mo of continuous in vitro culture and suggested that the decrease in metallo-protease is related to the loss of virulence. In the present study we purified the metallo-protease (200 kDa) from the pathogenic C. salrnositica and confirmed its proteolytic activities.…”
Section: Discussionmentioning
confidence: 78%
“…The proteolytic activity in the parasite lysate or in the purified fractions was detected using azocasein (AZC) as the substrate as described previously (Zuo & Woo 1997a). Briefly, 100 p1 of the sample was incubated with 0.5 m1 of AZC (10 mg ml-l) and 0.5 m1 phosphate buffer (0.1 M, pH 6.0) at 37°C for 2 h. 0.2 m1 of 50% trichloroacetic acid (TCA) was then added to terminate the reaction and the tube left to stand at 4°C for 30 min.…”
Section: O Inter-research 1997mentioning
confidence: 99%
See 3 more Smart Citations